2022
DOI: 10.3168/jds.2021-21618
|View full text |Cite
|
Sign up to set email alerts
|

DNA-based qualitative and quantitative identification of bovine whey powder in goat dairy products

Abstract: As one of the main ingredients in some milk powders, whey powder is sometimes added to pure goat milk products, which can cause health risks, economic fraud, and unfair competition of food industries. This study is the first to explore qualitative and quantitative methods to identify adulteration of bovine whey powder in goat dairy products based on DNA. We extracted DNA from whey powder using a modified DNA extraction method; this exhibited good quality and integrity, with purity of 1.53 to 1.75 and concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Dairy products are one of the important sources of nutrition for the human body. However, fraud—driven by profits—often occurs, such as shoddy and adulterated dairy products with high value [ 4 , 5 , 6 ]. Therefore, the development of selective and sensitive detection techniques is a key challenge for the detection of authentic food, especially dairy products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dairy products are one of the important sources of nutrition for the human body. However, fraud—driven by profits—often occurs, such as shoddy and adulterated dairy products with high value [ 4 , 5 , 6 ]. Therefore, the development of selective and sensitive detection techniques is a key challenge for the detection of authentic food, especially dairy products.…”
Section: Discussionmentioning
confidence: 99%
“…Driven by profits, fraud such as shoddy and adulterated dairy products with high value often occurs [ 4 , 5 , 6 ]. At present, the main adulterants in dairy products are nitrogen-containing compounds, vegetable proteins (such as soy protein) and animal proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Together with a growing demand and popularity of goat dairy products in general (Zhang et al, 2022), a growing demand for liquid goat whey has also been observed in Serbia. Liquid whey that appeared on the market recently, originated from both farm and industry cheese production.…”
Section: Introductionmentioning
confidence: 99%